IMPLEMENTATION OF REGULATION OF THE DIRECTOR GENERAL OF IMMIGRATION NUMBER IMI-459.GR.01.02 YEAR 2011 CONCERNING OPERATIONAL STANDARDS BORDER CONTROL MANAGEMENT PROCEDURES IN THE FRAMEWORK OF IMMIGRATION BANKING INSPECTION IN TANJUNG PERAK 2020 - Baginda Eka Pradana (Polteknik Imigrasi, 2019)
Border Control Management System (BCM) which is connected to the Immigration Management Information System (SIMKIM). SIMKIM is an information and communication technology systemused to collect, process, and present information to support operations, management and decision making in carrying out the Immigration Function. This study aims to determine the process of the Border Control Management (BCM) system immigration inspection, and the obstacles faced by the Tanjung Perak Immigration Checkpoint. This type of research is descriptive with a qualitative approach. The data collection techniques used were interviews, observation, and documentation. The informants used in this study were 2 informants. The main informant is the head of the TPI Tanjung Perak section. Supporting informants are immigration officials. The immigration check process of the Border Control Management System (BCM) at the Tanjung Perak Immigration Checkpoint is not connected online with the Immigration Management Information System (SIMKIM), it was found that at TPI Tanjung Perak there is no network connecting BCM with SIMKIM online. The obstacles faced are that there is no network that can connect online, and the budget for installing a new internet network can be budgeted next year.